Kontrol Suhu Rice Cooker dengan Metode Fuzzy Logic Sebagai Slow Cooker dan Memanaskan Makanan Menggunakan Aplikasi Android - Farlie Angriawan; Ratna Aisuwarya; Rian Ferdian (Universitas Andalas, 2020)
There is many electronic equipment that can facilitate the work in cooking. Some of these electronic equipment uses a large amount of electricity. For example in the use of electronic cooking tools such as microwaves, slow cookers and rice cookers. All three cooking utensils have more similar uses, namely in cooking and heating food. Therefore, it is combined into a rice cooker by using temperature control in the porridge cooking mode and setting the time for heating the food. In order to add the slow cooker feature to the rice cooker, the fuzzy logic method is used to control temperature and set the heating time on the microwave feature. On the use of a rice cooker, an Android application is made to select the desired cooking method. The results obtained are the features of slow cooker cooking porridge that is cooked for 2 hours the temperature will be stable at 60 minutes with an average temperature of ± 90.8 ° C, cooking porridge for 4 hours the temperature will be stable at 50 minutes with an average of average temperature ± 81.9 ° C, the cooking porridge for 6 hours the temperature will be stable in the 45th minute with an average temperature of ± 72.4 ° C. While in the microwave feature the results obtained for the length of time required to heat food, the more food heat to be produced.